2022
DOI: 10.3390/atmos13071095
|View full text |Cite
|
Sign up to set email alerts
|

Functional Kriging for Spatiotemporal Modeling of Nitrogen Dioxide in a Middle Eastern Megacity

Abstract: Long-term hour-specific air pollution exposure estimates have rarely been of interest in epidemiological research. However, this can be relevant for studies that aim to estimate the residential exposure for the hours that subjects mostly spend time there, or for those hours that they may work in another location. Here, we developed a model by spatially predicting the long-term diurnal curves of nitrogen dioxide (NO2) in Tehran, Iran, one of the most polluted and populated megacities in the Middle East. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…On top of that, we showed that the spatial pattern of PM 2.5 is not constant during the day, so hour-specific exposure is not necessarily proportional to the corresponding daily average. This observed pattern is also in line with a recently published study of nitrogen dioxide modeling in Tehran [10].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…On top of that, we showed that the spatial pattern of PM 2.5 is not constant during the day, so hour-specific exposure is not necessarily proportional to the corresponding daily average. This observed pattern is also in line with a recently published study of nitrogen dioxide modeling in Tehran [10].…”
Section: Discussionsupporting
confidence: 92%
“…The trend of PM 2.5 concentrations changes during the day at the monitoring stations and at the estimated maps, as depicted in Figures 2 and 5; they are tied with traffic regulations that restrict the commuting of heavy supply trucks in the megacity of Tehran to the hours between 10 p.m. and 6 a.m. [34,35]. A similar pattern for long-term diurnal changes in nitrogen dioxides was reported in a recently published paper, where the authors employed a functional extension of ordinary kriging [10]. Furthermore, this is in line with an emission inventory approach which showed that 85% of particle matter emissions in Tehran were sourced from heavy-duty vehicles [36].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations